Facial emotion processing and recognition among maltreated children: a systematic literature review - da Silva Ferreira, Gabriela C.; Crippa, José A. S.; de Lima Osório, Flávia (Frontiers in Psychology, 2014)
Exposure to maltreatment is associated with biological, psychological, and social development impairments in children. This systematic literature review sought to determine whether an association exists between child maltreatment and facial emotion processing and recognition. The search was conducted using the databases PubMed, PsycINFO, and SciELO using the following keywords: “maltreatment,” “adversity,” “neglect,” “sexual abuse,” “emotional abuse,” “physical abuse,” “child*,” “early,” “infant,” “face,” “facial,” “recognition,” “expression,” “emotion*,” and “impairment.” Seventeen articles were selected and analyzed. Maltreated children tended to exhibit less accuracy in global facial tasks and showed greater reactivity, response bias, and electrophysiological activation of specific brain areas in response to faces expressing negative emotions, especially anger. We concluded that the results of this review are exploratory and non-conclusive due to the small number of studies published and the wide variety of aims and procedures. Those shortcomings notwithstanding, the results indicate definite tendencies and gaps that should be more thoroughly explored in future studies.